Energy consumption of the countries in the context of economic development and energy transition. (November 2022) - Komarova, A.V.; Filimonova, I.V.; Kartashevich, A.A.
Abstract: The paper examines the dependence of economic growth on the level of energy consumption in various countries of the world, divided into groups according to the level of economic development and geographical location (macro-regions). It is shown that the impact of energy consumption on gross domestic product (GDP) is stronger in non-OECD countries than in the Organization for Economic Co-operation and Development (OECD) countries, which is explained by the extensive nature of economic development. This relationship is clearly seen in such macro-regions as the Asia-Pacific region, Africa, Central and South America. The energy intensity of the countries of the world is calculated, and the main trends for different groups of countries are analyzed.